PENGARUH GAYA KOMUNIKASI DAN GAYA KEPEMIMPINAN ASTA BRATA TERHADAP KINERJA BENDESA ADAT DI DESA ADAT BULELENG KECAMATAN BULELENG KABUPATEN BULELENG - kadek tedy mandala putra; I Nyoman Yoga Segara; Ida Ayu Tary Puspa (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2021)
This study aims to: (1) analyze the influence of Asta Brata's communication style and leadership style on the performance of the Bendesa Adat in the Buleleng Traditional Village, Buleleng District, Buleleng Regency; (2) describe the influence of communication style on the performance of the Bendesa Adat Buleleng; and (3) describe the influence of Asta Brata's leadership style on the performance of the Bendesa Adat Buleleng. This study uses a quantitative research design that uses the type or form of research that uses statistical calculations carried out through field data collection to Prajuru Desa and community leaders and the method used is the survey method. The data collection technique used is a questionnaire and then analyzed using regression analysis with the aim of determining the causal relationship between one variable and another. The results of the study show that communication style has a significant effect on the performance of the Bendesa Adat. The percentage of the contribution of the partial influence of the communication style variable on the performance of the traditional village leader is 60%. Then the leadership of Asta Brata has a significant effect on the performance of the Bendesa Adat. The percentage of the contribution of the partial influence of the Asta Brata leadership style variable on the performance of the traditional village leader is 30%. And the communication style and leadership style of Asta Brata have a significant effect on the performance of the Bendesa Adat. The percentage contribution of the simultaneous influence between the variables of communication style and Asta Brata's leadership style on the performance of the Bendesa Adat is 68%.